NILAI MORAL PADA FILM PENDEK JANGAN BACA PANCASILA KARYA RAFDI AKBAR - Erwin Ginting (Lembaga Pengembangan Kinerja Dosen, 2022)
The title of this research is Moral Values ​​in the Short Film Don't Read Pancasila by Rafdi Akbar. Film itself is a tool to convey various messages to the public or community with story media. The film Don't Read Pancasila tells the story of a family with a child named Sandy. As a child, Sandy grew up like children in general. But on the other hand, Sandy suffers from a syndrome called Asperger's or in other words called Autism, causing him trouble or difficulty from an early age, so that he is always seen as strange and stupid by many people including his friends because of his temperament and autistic nature. . The method used in this research is descriptive qualitative method. Meanwhile, the results obtained in this study are in the form of words, phrases, clauses, and sentences obtained in the short film Don't Read Pancasila by Rafdi Akbar. The data collection technique that the author did in this study used the listening and note-taking technique. This study aims to find the moral values ​​contained in the short film Don't Read Pancasila by Rafdi Akbar. While the results obtained in this research are displayed in the real reality, namely the existence of moral values ​​such as courage, humility, lying and compassion.